Metaphysics : a contemporary introduction - Loux, Michael J. (Routledge, 1998)
Metaphysics: Contemporary Readings is a comprehensive anthology that draws together leading philosophers writing on major themes in Metaphysics. Chapters appear under the headings: Universals, Particulars, Modality and Possible Worlds, Causation, Time and Realism and Anti-realism. The book is highlyaccessible and user-friendly and provides a broad-ranging exploration of the subject. Ideal for the philosophy student, this reader will prove essential reading for any metaphysics course.